Pengaruh Model Pembelajaran Student Team Achievement Division Berbantu Media Diorama Terhadap Hasil Belajar IPA - Eva Aprilia Nur Pratiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine the effect of the Student Team Achievement Divisionlearning model assisted by Diorama media on science learning outcomes. This study wasconducted on fifth grade students at SD N Payaman 1, Magelang Regency.This type ofresearch is Pre Experimental Designs with the research design used One Group PretestPosttest Design. The sample of this study was the fifth grade students at SD N Payaman1, totaling 18 students. The sampling technique used in this research is saturatedsampling. The method of collecting data was using multiple choice tests, then analyzedusing the Piared Sample T-Test with the help of IBM SPSS Statistics 24.Based on the dataanalysis method used by the Paired Sample T Test, the Asymp Sig (2-tailed) is 0.000 andthe t-count value is 14.028 > t table 1.734, so it can be concluded that Ho is rejected andHa is accepted, which means that there is a positive and significant effect on theapplication of the learning model. Student Team Achievement Division on science learningoutcomes for fifth grade students at SD N Payaman 1, Magelang Regency.